Production of mannan-degrading enzymes from Aspergillus niger and Sclerotium rolfsii using palm kernel cake as carbon source. - Abd. Aziz, Suraini; Ab Razak, Nor Asma; Musa, Mohamed Hanafi; Hassan, Mohd Ali (Academic Journals Inc., 2009)
The aim of this study is to produce and profile the mannan-degrading enzymes from local fungal isolates by submerged fermentation and saccharification of PKC. Results showed that Aspergillus niger and Sclerotium rolfsii can produce mannan-degrading enzymes. The fungi were grown in submerged fermentation of PKC to produce mannan-degrading enzymes. The highest alpha-galactosidase was obtained on day 13 of fermentation (0.128 U mL-1) when using A. niger and on day 18 (0.126 U mL-1) when using S. rolfsii. Analysis also showed that enzyme activities for beta-mannanase using S. rolfsii were the highest at day 17 (3.166 U mL-1) and for A. niger (2.482 U mL-1) at day 8. Meanwhile the highest beta-mannosidase were obtained at day 16 for A. niger (0.128 U mL-1) and for S. rolfsii at day 16 (0.116 U mL-1).